1996
DOI: 10.4315/0362-028x-59.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Listeria monocytogenes, Listeria seeligeri, and Listeria innocua Assayed with In Vitro Murine Macrophagocytosis

Abstract: The survival of virulent and avirulent Listeria species internalized in cells of a murine macrophage-like cell line, RAW264.7, was monitored. Mouse macrophage cells (ca. 5 × 105/ml) suspended in fresh RPMI medium 1640 containing fetal bovine serum were mixed with 5 × 107 to 5 × 108 Listeria cells per ml and incubated 1 h at 37°C with CO2-enriched air. Gentamicin (10 μg/ml) was added to kill bacteria not internalized by the cells. At 2, 4, and 6 h postinfection, 10-μl amounts of the suspensions were lysed in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…6), also consistent with previous data (25). These findings are also consistent with a previous study that showed a lack of proliferation of L. seeligeri in another macrophage cell line (9). The L. monocytogenes ⌬prfA strains expressing prfA LM under the control of the P1prfA-and-P2prfA promoter region (the ⌬prfA prfA LM356 strain) or under the control of the P1P2prfA region and the upstream plcA promoter (the ⌬prfA PplcA prfA LM strain) showed intracellular Table 3 for strain designations).…”
supporting
confidence: 93%
“…6), also consistent with previous data (25). These findings are also consistent with a previous study that showed a lack of proliferation of L. seeligeri in another macrophage cell line (9). The L. monocytogenes ⌬prfA strains expressing prfA LM under the control of the P1prfA-and-P2prfA promoter region (the ⌬prfA prfA LM356 strain) or under the control of the P1P2prfA region and the upstream plcA promoter (the ⌬prfA PplcA prfA LM strain) showed intracellular Table 3 for strain designations).…”
supporting
confidence: 93%
“…Cytotoxicity assays conducted by previous researchers did not include many L. ivanovii strains in their test panel (Del Corral et al 1990 ;Bunduki et al 1996 ;Dallas et al 1996). In this study, it was found that six strains of L. ivanovii had some cytotoxic effect (as indicated by AP release) on Ped-2E9 cells and five strains had a significantly lower cytotoxic effect than L. monocytogenes strains (Fig.…”
Section: ------------------------------------------------------------mentioning
confidence: 69%
“…Rapid detection as well as pathogenicity testing of this organism is essential for controlling incidence of listeriosis. Various mammalian cell lines have been tested for their efficacy to determine virulence of L. monocytogenes in vitro, including intestinal cells (Del Corral et al 1990 ;Pine et al 1991 ;Schlech et al 1994 ;Bunduki et al 1996), fibroblasts (Siddique 1969), and macrophage cells (Portnoy et al 1988 ;Dallas et al 1996). In these cell lines, cytotoxicity was determined by the invasion assay or the trypan blue exclusion test, or by observing morphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…As a substitute, use of various tissue culture cell lines have been proposed by several researchers to test the cytopathogenicity of Listeria spp. (Del Corral et al 1990;Pine et al 1991;Bhunia et al 1994;Dallas et al 1996). Cytotoxicity effects on many of these cell lines were often determined by differential trypan blue staining or intracellular bacterial counts assay.…”
Section: Introductionmentioning
confidence: 99%